Land property in Sub-Saharan Africa : legal essay on a totem of State - (:unkn) unknown (My University, 2022)
This thesis focuses on land property in sub-Saharan Africa being deliberate in its dealing with the 29 countries of that region. This work offers a conceptual explorationof a right that the sub-Saharan States have taken as a totem as to identifying themselves with the sovereign power they claimed before their institution. Land ownership in this geographical area, determined by its great diversity of normative influences and the significance of modes of social regulation that are mostly foreign to the legal phenomenon, has entered the legal order without really returning to order. Legally consecrated in all the countries studied, it still faces tensions that hinder both its establishment and its circulation. The anthropological modeling of the right to property as a totem of the state is presented through the process of its legalization between the colonial trauma and the independence of African states (First Part). The legal functionalities of this state totem in the hands of private persons are studied from the angle of the title split between the social fact and the legal fact, the patrimonial and the fiduciary, but also,between the current state monopoly and the actualization of individual sovereignty heralded by the rise of new technologies (Second Part).
Keywords: African Research